Novel Biogenic Silver Nanoparticle-Induced Reactive Oxygen Species Inhibit the Biofilm Formation and Virulence Activities of Methicillin-Resistant Staphylococcus aureus (MRSA) Strain - Hamida, Reham Samir; Ali, Mohamed Abdelaal; Goda, Doaa A.; Khalil, Mahmoud Ibrahim; Al-Zaban, Mayasar Ibrahim (Frontiers in Bioengineering and Biotechnology, 2020)
Emerging antibiotic-resistant bacteria result in increased mortality and have negative economic impacts. It is necessary to discover new strategies to create alternative antibacterial agents that suppress the bacterial resistance mechanism and limit the spread of serious infectious bacterial diseases. Silver nanoparticles may represent a new medicinal agents as alternative antibiotics affect different bacterial mechanisms such as virulence and resistance. In addition to that of silver nitrate (AgNO3) and ampicillin, for the first time, the inhibitory effect of silver nanoparticles synthesized using Desertifilum sp. (D-SNPs) was evaluated against five pathogenic bacteria using the agar well diffusion method. Also, the influence of D-SNPs and AgNO3 on bacterial antioxidant and metabolic activities was studied. The antibacterial activity of D-SNPs and AgNO3 against methicillin-resistant Staphylococcus aureus (MRSA) strains was studied at the morphological and molecular level. D-SNPs and AgNO3 have the ability to inhibit the growth of the five bacterial strains and resulted in an imbalance in the CAT, GSH, GPx and ATPase levels. MRSA treated with D-SNPs and AgNO3 showed different morphological changes such as apoptotic bodies formation and cell wall damage. Moreover, both caused genotoxicity and denaturation of MRSA cellular proteins. Additionally, TEM micrographs showed the distribution of SNPs synthesized by MRSA. This result shows the ability of MRSA to reduce silver nitrate into silver nanoparticles. These data indicate that D-SNPs may be a significant alternative antibacterial agent against different bacteria, especially MDR bacteria, by targeting the virulence mechanism and biofilm formation, leading to bacterial death.